Mitochondrial association, protein phosphorylation, and degradation regulate the availability of the active Rab GTPase Ypt11 for mitochondrial inheritance - Lewandowska, Agnieszka (The American Society for Cell Biology, 2013)
The Rab GTPase Ypt11 is a Myo2-binding protein implicated in mother-to-bud transport of the cortical endoplasmic reticulum (ER), late Golgi, and mitochondria during yeast division. However, its reported subcellular localization does not reflect all of these functions. Here we show that Ypt11 is normally a low-abundance protein whose ER localization is only detected when the protein is highly overexpressed. Although it has been suggested that ER-localized Ypt11 and ER–mitochondrial contact sites might mediate passive transport of mitochondria into the bud, we found that mitochondrial, but not ER, association is essential for Ypt11 function in mitochondrial inheritance. Our studies also reveal that Ypt11 function is regulated at multiple levels. In addition to membrane targeting and GTPase domain–dependent effector interactions, the abundance of active Ypt11 forms is controlled by phosphorylation status and degradation. We present a model that synthesizes these new features of Ypt11 function and regulation in mitochondrial inheritance.